2011
DOI: 10.1111/j.1365-2648.2011.05866.x
|View full text |Cite
|
Sign up to set email alerts
|

More than meets the eye. Feminist poststructuralism as a lens towards understanding obesity

Abstract: It is imperative that we continue to question our everyday nursing practices as we work to support clients, especially those who feel marginalized. This focus on power relations and reflective practice can give direction to new possibilities for change in obesity management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Based on our findings, these were the use of food as a coping mechanism and source of mental distress; blame and shame in interpersonal relationships; condemnation and lack of psycho-social care within the healthcare system; and the negative impact of the social stigma of obesity. Weight bias directed at those living with obesity was an overarching theme and main source of the negative interactions that caused deterioration of the participants’ mental well-being, as we have found in our previous studies (Aston et al, 2011; Kirk et al, 2014; Price et al, 2015). While HCPs could identify the individual- and organizational-level issues as barriers to promoting the positive mental well-being of their clients, at times they appeared to lack awareness of the social determinants of health or the need to look beyond the individualistic healthcare model to provide support for their clients.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Based on our findings, these were the use of food as a coping mechanism and source of mental distress; blame and shame in interpersonal relationships; condemnation and lack of psycho-social care within the healthcare system; and the negative impact of the social stigma of obesity. Weight bias directed at those living with obesity was an overarching theme and main source of the negative interactions that caused deterioration of the participants’ mental well-being, as we have found in our previous studies (Aston et al, 2011; Kirk et al, 2014; Price et al, 2015). While HCPs could identify the individual- and organizational-level issues as barriers to promoting the positive mental well-being of their clients, at times they appeared to lack awareness of the social determinants of health or the need to look beyond the individualistic healthcare model to provide support for their clients.…”
Section: Discussionsupporting
confidence: 61%
“…The original research was conducted using feminist poststructuralism (Butler, 1992; Cheek, 2000; Foucault, 1983; Scott, 1992) as the guiding methodology. Feminist poststructuralism focuses on understanding how personal experiences are constructed through social and institutional discourses through relations of power (Aston, Price, Penney, & Kirk, 2011). Three cross-cutting themes were identified across the groups of participants, including aspects of blame relating to obesity development, tensions between obesity management and prevention, and a prevailing discourse that was not supportive to the management of obesity (Kirk et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discourses (repeated understandings, knowledges, practices) (Foucault & Gordon, 1980;Foucault, 1972;Foucault, 1982) shape not only how a person experiences obesity and their self-identity (see, Wadden & Didie, 2003), but they also shape how others might understand the issue. Since obesity is primarily represented as a matter rooted in personal choice and autonomy, this renders those persons experiencing obesity as persistently stigmatized, misunderstood and held personally responsible for their body weight (Aston, Price, Kirk, & Penney, 2012;Puhl & Kyle, 2014;Puhl et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of the health professional-client relationship is particularly critical within obesity management (Aston et al, 2012;; however, this relationship may be compromised, due to the perpetuation of bias and stigma among health professional groups towards those persons living with obesity. Numerous studies have identified health professional groups, which include physicians, nurses, dietitians, and psychologists, as describing those living with excess body weight as persons lacking self-control or willpower, lazy and with poor compliance (Harvey, Summerbell, Kirk, & Hill, 2002;Puhl, Wharton, & Heuer, 2009;Puhl & Brownell, 2001).…”
Section: Introductionmentioning
confidence: 99%